Downregulation of CPA4 inhibits non small–cell lung cancer growth by suppressing the AKT/c‐MYC pathway. Issue 11 (9th August 2019) - Fu, Yangyang; Su, Lihuang; Cai, Mengsi; Yao, Boyang; Xiao, Sisi; He, Qinlian; Xu, Le; Yang, Lehe; Zhao, Chengguang; Wan, Tingting; Shao, Lianyou; Wang, Liangxing; et al.
Abstract: Carboxypeptidase A4 (CPA4) is a member of the metallocarboxypeptidase family. A previous study indicated that CPA4 may participate in the modulation of peptide hormone activity and hormone‐regulated tissue growth and differentiation. However, the role of CPA4 in lung tumorigenesis remains unclear. Our study revealed that CPA4 expression was higher in both lung cancer cells and tumor tissues. We performed 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide assays, colony‐formation assays, and Cellomics ArrayScan Infinity analysis to demonstrate that CPA4 knockdown inhibited non small–cell lung cancer (NSCLC) cell proliferation. Conversely, ectopic expression of CPA4 enhanced lung cancer cell proliferation. Consistent with these observations, we generated xenograft tumor models to confirm that CPA4 downregulation suppressed NSCLC cell growth. Mechanistically, we revealed that CPA4 downregulation may induce apoptosis and G1‐S arrest by suppressing the protein kinase B/c‐MYC pathway. These results suggest that CPA4 has an oncogenic effect on lung cancer growth. Taken together, we identified a novel gene in lung cancer that might provide a basis for new therapeutic targets.